Erratum: On equilibrium intensive thermodynamic properties of composed p-particles in many-body systems (Article in Int J Quantum Chem (2001) Vol. 85 (63)) - Bochicchio, R.C. (2002)
Fil:Bochicchio, R.C. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.